Proses Adaptasi Komunitas Wisata untuk Mencapai Ketahanan di Kampung Wisata Rejowinangun Yogyakarta Selama Pandemi Covid-19 - Asyila, Safira (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2023)
The social and economic aspects of Rejowinangun Tourism Village, which comprises five tourism clusters, were significantly impacted by the COVID-19 pandemic. This study seeks to comprehend how the tourism community in Rejowinangun Tourism Village reacted to the crisis caused by the COVID-19 pandemic and the issues mentioned above. Conducting this research is crucial to identifying the determinants of tourism resilience in tourist villages amidst the COVID-19 pandemic. This study employs a qualitative descriptive methodology. The data collection procedure comprised a literature review, semi-structured interviews, and field observations. The tourism industry reacted to the COVID-19 pandemic by implementing human resource capacity-building initiatives, demonstrating adherence to health protocols, and implementing digitization innovations. In addition to the tourism village community comprising the community and the tourism cluster, the government plays a significant role in shaping the tourism community's resilience in the face of the COVID-19 pandemic.